Application of big Data in e-Governance - Bhandari, Reg Bahadur (Patan Prospective Journal, 2023)
Nepal is moving towards digitization. In Nepal federal, province and Local government are steadily moving towards digitizing all the government departments, scheme and services. e-Government is defined as an effort created, managed and implemented by public entities to use information and communication technologies (ICTs) to improve delivery of public services and increase public and democratic participation. Three tier government of Nepal is moving towards achieving good governance through e-governance and utilization of big data for decision making and predication. The spread of e governance initiatives has had a positive impact on the quality of governance. Geographical, social, & economic disparities are the biggest barriers for full-fledged e-governance. Illiteracy and IT Illiteracy, lack of ICT infrastructure, security and privacy of personal and financial data are other constraints. The aim of this paper is to identify the application and utilization of big Data to Transform Government to e-Government, the issues, challenges and obstacles ahead. The study provides a framework for e-governance in Nepal by analyzing the its essential application and role in achieving good governance using big data.